Change, anxiety and exclusion in the post‐colonial reconfiguration of Franco‐Mauritian elite geographies. Issue 3 (22nd October 2013) - Salverda, Tijo; Hay, Iain
<x xml:space="preserve">Abstract</x> Using the example of Mauritius, this paper seeks to enhance our understanding of how elites reorganise their environs when their position and power are threatened. In 1968 Mauritius became independent and for Franco‐Mauritians, the island's former white colonial elite, this meant that a regime favourable to their dominant position ended. This paper outlines ways in which Franco‐Mauritians have transformed their everyday geographies in the face of this change. We suggest that feelings of anxiety and the consequent desire to regain some measure of control have influenced Franco‐Mauritians' (re)shaping of exclusive cultural, educational, recreational, and residential enclaves to create new patterns of exclusion and segregation. We suggest, moreover, that such enclaves are simultaneously – and paradoxically – a root of both continuing anxiety and the foundation of continued exclusivity.